If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -22 = -7 + 3y Solving -22 = -7 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. -22 + -3y = -7 + 3y + -3y Combine like terms: 3y + -3y = 0 -22 + -3y = -7 + 0 -22 + -3y = -7 Add '22' to each side of the equation. -22 + 22 + -3y = -7 + 22 Combine like terms: -22 + 22 = 0 0 + -3y = -7 + 22 -3y = -7 + 22 Combine like terms: -7 + 22 = 15 -3y = 15 Divide each side by '-3'. y = -5 Simplifying y = -5
| -59+3x=2x+21 | | 5(0)+y=20 | | -7(-5n-2)=119 | | 42=34+q | | Log(x-6)=2 | | -1+6y=14 | | 8(4)(7)-9(3)+4(4)= | | 7x+5=5x-5 | | 10010001001002030+3-10= | | 3x+5=-8(6-5x) | | 11x-47-x=103 | | 4v=8v+32 | | 10m+12n+5m+3n+35= | | 2x-42-7x=84 | | 5x+2(1.5)=10 | | 49-9x+5x=27 | | 10000000000000000000000000000+e= | | 12-7x+4x=27 | | x+7.8=3 | | 2(y+3)=a | | 5(-4)+2y=10 | | 3x+9x-83=73 | | 6.5x+3.5y=9.5 | | 5x+75=10x-5 | | a=2(y+3) | | 6x+4x-97=103 | | 12=5x-9-2x | | -4y-42-3y=5y | | 11x-118-x=38 | | 12x-6x-86=82 | | 6x-8x-22=24 | | f(x)=4x^2-4x-8 |